1988
DOI: 10.1044/jshd.5301.94
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Symbolic Communication in Persons with Severe Retardation

Abstract: For persons with severe retardation, learning to communicate symbolically is a complex long-term process requiring the coordination of many components to succeed. Three of four institutionalized adolescents and young adults with severe retardation who participated in this study learned to use lexigrams to request foods and, subsequently, objects. Although their request skill did not initially generalize to labeling and to comprehension tasks, additional request experience with lexigrams resulted in consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…For example, SB verbal behavior has been called an "aided" (Romski, et al, 1988;Sigafoos & Iacono, 1993) The tact relation as defined by Skinner (1957) is "a verbal operant in which a response of given form is evoked (or at least strengthened) by a particular object or event or property of an event. We account for the strength by showing that in the presence of the object or event a response of that form is characteristically reinforced in a given verbal community" (p. 82).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SB verbal behavior has been called an "aided" (Romski, et al, 1988;Sigafoos & Iacono, 1993) The tact relation as defined by Skinner (1957) is "a verbal operant in which a response of given form is evoked (or at least strengthened) by a particular object or event or property of an event. We account for the strength by showing that in the presence of the object or event a response of that form is characteristically reinforced in a given verbal community" (p. 82).…”
Section: Notesmentioning
confidence: 99%
“…First, as some researchers have recently noted, there appears to be an increase in the use of SB techniques (e.g., communication boards, PECS) with developmentally-delayed and disabled populations (Bondy & Frost, 1993;Shafer, 1993;Shane & Bashir, 1980;Sundberg, 1993;Sundberg & Sundberg, 1990). This increase has not been accompanied by much empirical research (Shafer, 1993;Sundberg & Sundberg, 1990), and published studies are often in the form of case studies (Romski, Sevcik & Pate, 1988).…”
mentioning
confidence: 99%
“…Persons with mental retardation often have great difficulty acquiring arbitrary matching to sample, a form of conditional discrimination (Mcllvane, Dube, Kledaras, Iennaco, & Stoddard, 1990;Romski, Sevcik, & Pate, 1988), even though they may readily demonstrate identity matching (K. Saunders & Spradlin, 1989. We have previously suggested that these difficulties can be due to deficits in prerequisite component skills.…”
mentioning
confidence: 99%
“…A study by Romski, Sevcik, and Pate (1988) illustrates a similar concern. They trained learners with mental retardation to select lexigrams on a computer keyboard to mand food items.…”
Section: Establishing Performance Across Untrained Stimulus Conditionsmentioning
confidence: 91%